JOHN H. SLATE and KAYE LANNING MINCHEW, Managing Local Government Archives - Woodley, Charlotte (Archivaria, 2018)
Managing Local Government Archives. John H. Slate and Kaye Lanning Minchew. Lanham, MD: Rowman & Littlefield, 2016. xix, 166 pp. ISBN 978-1-4422-6394-9